Mixed viral infection constrains the genome formula of multipartite cucumber mosaic virus - Boezen, Dieke; Vermeulen, Maritta; Johnson, Marcelle L.; van der Vlugt, René A. A.; Malmstrom, Carolyn M.; Zwart, Mark P. (Frontiers in Virology, 2023)
Many plant viruses have a multipartite organization: multiple genome segments packaged into separate virus particles. The genome formula describes the relative frequencies of all viral genome segments, and previous work suggests rapid changes in these frequencies facilitate virus adaptation. Many studies have reported mixed viral infection in plants, often resulting in strong virus-virus interactions. Here we test whether mixed infections with tripartite alfalfa mosaic virus (AMV) and monopartite potato virus Y (PVY) affect the genome formula of the tripartite cucumber mosaic virus (CMV), our experimental model. We found that CMV titer was reduced in mixed infection with its tripartite Bromoviridae relative AMV, and in triple infection with both AMV and PVY, indicating notable virus-virus interactions. The variability of the CMV genome formula was significantly reduced in mixed infection (CMV & AMV, CMV & PVY, CMV & AMV & PVY) compared to single (CMV only) infection. These observations lead to the surprising conclusion that mixed infection with two distinct viruses constrains the CMV genome formula. It remains unclear how common these effects are for different combinations of virus species and strains, and what the underlying mechanisms are. We therefore extended a simulation model to consider three putative scenarios in which a second virus affects the genome formula. The simulation results also suggest that shifts in the genome formula occur, but may not be widespread due to the required conditions. One scenario modeled -coinfection exclusion through niche differentiation -is congruent with the experimental data, as this scenario leads to a reductions in genome formula variability and titer of the multipartite virus. Whereas previous studies highlight host-species effects, our results indicate the genome formula is also affected by mixed infection, suggesting there is a broader set of environmental cues that affect the genome formula.